A toolbox for secondary quality control on ocean chemistry and hydrographic data. (8th August 2015) - Lauvset, Siv K.; Tanhua, Toste
Abstract: High quality, reference measurements of chemical and physical properties of seawater are of great importance for a wide research community, including the need to validate models and attempts to quantify spatial and temporal variability. Whereas data precision has been improved by technological advances, the data accuracy has improved mainly by the use of certified reference materials (CRMs). However, since CRMs are not available for all variables, and use of CRMs does not guarantee bias‐free data, we here present a recently developed Matlab toolbox for performing so‐called secondary quality control on oceanographic data by the use of crossover analysis. This method and how it has been implemented in this toolbox is described in detail. This toolbox is developed mainly for use by sea‐going scientists as a tool for quickly assessing possible bias in the measurements that can—hopefully—be remedied during the expedition, but also for possible post‐cruise adjustment of data to be consistent with previous measurements in the region. The toolbox, and reference data, can be downloaded from the Carbon Dioxide Information Analysis Center (CDIAC):http://cdiac.ornl.gov/ftp/oceans/2nd_QC_Tool_V2/ .